The Preference of Millennial in Surabaya Towards Workspace Characteristics - Juwono, Chrisna Hadi; Kwanda, Timoticin; Anastasia, Njo (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2022)
Millennial generation grows in the advance of information technology and dominates the productive age in Surabaya City. Their capability in operating technology makes work activities more efficient, as a result the need for concentration in workspaces could be reduced. Previous research focused on millennial’s workspace, but it was limited to one workspace. Therefore, this research is conducted to find the millennial’s preferences in the type of workspace character. Data was collected by questionnaire. Hypothesis testing using ANOVA and Kendall’s concordance test. The result showed that the workspace optimize concentration is less demanded. Millennial are comfortable in workspace that collaborate with the other workers, such as team rooms, although younger millennials need more concentration than older millennials.